2021
DOI: 10.1007/s11695-020-05193-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on COVID-19: a Multicentric Study from a High Incidence Area

Abstract: Introduction The favorable effects of bariatric surgery (BS) on overall pulmonary function and obesity-related comorbidities could influence SARS-CoV-2 clinical expression. This has been investigated comparing COVID-19 incidence and clinical course between a cohort of patients submitted to BS and a cohort of candidates for BS during the spring outbreak in Italy. Materials and Methods From April to August 2020, 594 patients from 6 major bariatric centers in Emilia-Romagna were administered an 87-item telephonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…It is important to finalize strategies and procedures to prevent SARS-CoV-2 infection among GPs, for example, specific guidelines for GPs to safely guarantee care for patients during the spread of COVID-19. Another input could be the introduction of telemedicine procedures to reduce direct contact with patients [10,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to finalize strategies and procedures to prevent SARS-CoV-2 infection among GPs, for example, specific guidelines for GPs to safely guarantee care for patients during the spread of COVID-19. Another input could be the introduction of telemedicine procedures to reduce direct contact with patients [10,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Severe obesity could promote the clinical expression of influenza viruses, as recently reported for Sars-CoV-2 infection [19,20]. Obesity is in fact characterized by chronic low-grade inflammation, with subsequent impairment of the immune system, and it is also associated with reduced lung function and decreased respiratory compliance, leading to higher risk of obstructive syndrome and pneumonia [5,6].…”
Section: Dear Editormentioning
confidence: 83%
“…In a recent systematic review on obesity and COVID-J o u r n a l P r e -p r o o f 19, obesity was shown to have a significant association to higher COVID-19 infection rates (OR 1.50, P<0.001), more severe COVID-19 disease (OR 3.13, 95%; P=0.005) and higher mortality (OR 1.36, 95% P = 0.006) 43 . Bariatric surgery again has an important role in managing obesity-related COVID-19 complications, with one multi-center study finding that patients who have undergone bariatric surgery 12 months or earlier developed less severe COVID-19-related symptoms than subjects who were currently obese 46 . Therefore, while the COVID-19 pandemic justly halted elective bariatric surgeries, efforts must be made to prioritize bariatric surgeries once it is practical to do so 47 .…”
Section: Medical Benefits Of Reducing Obesity In the Covid-19 Eramentioning
confidence: 99%